VALIDITY OF INSTRUMENTS AS MEASURING INSTRUMENT EVALUATION PROGRAM ON THE JOB TRAINING STUDENTS SMK NEGERI 1 CARIU BOGOR REGENCY - Sefrianto; Aip Badrujaman; Komarudin Komarudin (LPPM Universitas Negeri Jakarta, 2020)
This research is part of the preparation before evaluating On the Job Training program. The goal is to validate the instrument before used as a raw instrument to obtain field data. This research is carried out with quantitative approach. The data is collected by using questionnaire instruments to evaluate the impact of evaluation on the job training program at the behavior, outcome levels, and results. The instrument is tested on 30 respondents, namely Honda Putra Merdeka Cibubur, Honda Lestari Motor Cariu and Honda Citra Indah Jonggol. The test validity of the instrument using the product moment correlation formula. The results of the study show not all tested instruments are valid. Out of 35 instruments tested, 4 items of instruments are invalid. The instrument is in the dimensions of precision and work accuracy, increase in company revenue, and the level of curiosity at work. The result of the instrument validity concludes that the instrument that can be used to evaluate the on the job training program is as many as 31 items with the reliability value that can be received in a very good category of 0.928.